Fatigue crack behavior on a Cu-Zn-Al SMA (Fracture and Structural Integrity, 2014)
In recent years, mechanical property of many SMA has improved in order to introduce these alloysin specific field of industry. Main examples of these alloys are the NiTi, Cu-Zn-Al and Cu-Al-Ni which are usedin many fields of engineering such as aerospace or mechanical systems. Cu-Zn-Al alloys are characterized bygood shape memory properties due to a bcc disordered structure stable at high temperature called ?-phase,which is able to change by means of a reversible transition to a B2 structure after appropriate cooling, andreversible transition from B2 secondary to DO3 order, under other types of cooling. In ?-Cu-Zn-Al shapememory alloys, the martensitic transformation is not in equilibrium at room temperature. It is therefore oftennecessary to obtain the martensitic structure, using a thermal treatment at high temperature followed byquenching. The martensitic phases can be either thermally-induced spontaneous transformation, or stressinduced,or cooling, or stressing the ?- phase. Direct quenching from high temperatures to the martensite phaseis the most effective because of the non-diffusive character of the transformation. The martensite inherits theatomic order from the ?-phase. Precipitation of many kinds of intermetallic phases is the main problem oftreatment on cu-based shape memory alloy. For instance, a precipitation of ?-phase occurs in many lowaluminum copper based SMA alloy and presence of ?-phase implies a strong degradation of shape recovery.However, Cu-Zn-Al SMA alloys characterized by aluminum contents less than 5% cover a good cold machiningand cost is lower than traditional NiTi SMA alloys. In order to improve the SMA performance, it is alwaysnecessary to identify the microstructural changing in mechanical and thermal conditions, using X-Ray analyses.In this work a Cu-Zn-Al SMA alloy obtained in laboratory has been microstructurally and metallographicallycharacterized by means of X-Ray diffraction and Light Optical Microscope (LOM) observations. Furthermorea fatigue crack propagation and fracture surface scanning electron microscope (SEM) observations have beenperformed in order to evaluate the crack path and the main crack micromechanisms.
Keywords: Fatigue crack propagation